Does Consumption Lag Behind Incomes? - Tinbergen, J. (The Review of Economics and Statistics, 1942)
CONSURlPTIONT H E fact that consumption outlay of indi- viduals as well as of groups of individuals depends on their income is well known.Although this statement will hardly be doubted, it may be tested statistically from family budget statistics, as has been done by various investigators.These statistics can show only that consumption outlay by different people, having different incomes a t the same moment, depends on income.Consumption outlay by the same family in different years, showing varying income, will not necessarily depend on income in the same way that is shown-by family budget statistics.This latter relation plays a highly important r61e in the causation of business cycles, a fact perhaps most stressed by Rlr.Keynes, who created the term "propensity to consume" and who used this notion in various deductions.The importance of the propensity to consume for the quantitative approximation of some business-cycle problems has led a number of authors to measurements of that coefficient.How large the propensity to consume may be is not the only important question.Another question is "What lag exists between income changes and changes in consumption outlay?"Tke longer this lag, the more slowly will the economic system react to changes in income and the longer, other things being equal, will be the process of adjustment (e.g., a business cycle).The answer to this question -put by Mrs. Gilboy in this REVIEW -cannot be given by family budyet data, as already stated.The only pos ible method of securing an answer is by use of t i n e series.The use of time series, however, a1wzj.simplies the difficulty that a number of cctcris pasibus clauses are no longer fulfilled.S o t only changes in income are the causes of any given changes in consumption outlay; other